Analisis Literasi Zakat, Infaq Dan Shadaqah Melalui Penggunaan Mobile Banking - Pulungan, Ira Andriani; Harahap, Darwis; Alfadri, Ferri; Wardana, Ahmad (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2023)
AbstractAdvances in information and communication technology are reflected in PT. BSI KCP Gunung Tua, which is developing their services by offering mobile banking services, however customers still lack knowledge in using them because many customers do not want to know about banking developments. This research uses a qualitative approach, namely research carried out by observing surrounding phenomena and analyzing them using scientific logic. This research used snowball sampling, the data collection instruments used were observation, interviews and documentation. The data analysis used is descriptive qualitative. The results of this research show that customer literacy regarding zakat infaq and shadaqah is very good because customers know zakat in general, customers also know the calculation of zakat, the objects and impacts of zakat. However, customer literacy is still minimal regarding mobile banking and only a few people know about it, but after opening an account at BSI KCP Gunung Tua they can find out.